Nootropic effect of neferine on aluminium chloride–induced Alzheimer's disease in experimental models. Issue 2 (20th December 2019) - Yin, Shuaizeng; Ran, Qin; Yang, Jin; Zhao, Yuhua; Li, Chenyu
Abstract: Alzheimer's disease (AD) is an age‐associated neurodegenerative disease, which is developed by oxidative stress and acetylcholine contraction in the synaptic cleft of the neurons. This leads to dementia, memory loss, and decrease in learning ability and orientation. In this research work, we aimed to explore the neuroprotective effect of neferine on AlCl3 ‐induced AD in rats. The results of our study revealed that the increased reactive oxygen species (ROS) and nitric oxide in the hippocampus leads to the development of AD in the rats. The oral treatment of neferine done the following occurrences such as; it potentially inhibited the ROS formation and acts as a scavenging molecule by preventing the neurodegeneration. It also improved the memory and learning ability to complete the maze activity in the AD rats and significantly increased the antioxidants superoxide dismutase, catalase, and reduced glutathione in neferine treated AD rats. It aggressively declined the activity of acetylcholine esterase and Na + K + ATPase in the neurodegenerative rat models. The gene expression pattern of neuroinflammatory cytokines such as tumor necrosis factor α (TNF‐α), interleukin‐6 (IL‐6), and interleukin‐1β (IL‐1β) were decreased in the neferine‐treated rats. The neuroinflammatory proteins such as inducible nitric oxide (iNOS), cyclooxygenase‐2 (COX‐2), and nuclear factor kappa β (Nf‐κβ) were decreased and Nf‐κβ inhibitor IKBα was increased in the neferine‐treated AD rats. Finally, the histology study proved that the neferine treatment possibly prevents neurodegeneration in the hippocampus tissue of the AD models. Hence, these all findings concluded that the neferine could be a potential neuropreventive as well as neurodegenerative therapeutic compound in neurological and cognitive dysfunction.